Assessment of plastic rotation and applied load in reinforced concrete, steel and timber beams using image-based analysis. (1st November 2019) - Carmo, Ricardo N.F.; Valença, Jonatas; Bencardino, Francesco; Cristofaro, Stefano; Chiera, Domenico
Highlights: Prediction of the applied load using only images. Curvature assessment using photogrammetry. Plastic rotation and ductility determined through a different methodology. Contribution to decrease the gap between the photogrammetry and the structural analysis. Abstract: The application of image-based methods for structural and material monitoring can significantly improve the analysis of their behavior in laboratorial and real situations. This paper presents a methodology based on photogrammetry and image processing aiming to: (i) estimate the bending moment and the applied load on steel and timber beams, using only digital images; (ii) evaluate the ductility of reinforced concrete (RC) beams, a key-parameter to understand the behavior of the beams near failure. The photogrammetry was used to obtain the highly discretized shape of the deformed beams under a specific load, an essential step to calculate the curvature of the beams. Additionally, for RC beams, the cracking pattern was also mapped and characterized using image processing. The methodology was validated by monitoring two series of experimental tests: (i) four different steel and timber beams tested and analyzed in the linear elastic range; and (ii) five different lightweight RC beams tested up to failure. The results show a good reliability of photogrammetry-based approach to calculate the curvature in the linear elastic range. Further improvements are required for compute the plastic rotation in the case of RC beams. The study presented highlights the advantages of using image-based methods for monitoring the behavior of materials and structures, such as: are contactless and cost-effective solutions, enable high discretization of the deformations, evaluation up to failure, and delivery reliable results.